PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA MELALUI PENDEKATAN KONSTRUKTIVISME DI SEKOLAH DASAR NEGERI 19 PASIR TINGGI - Nuraida, Nuraida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Through this research, the writer applies Konstruktivisme in processes learning or there are many student. Observational stage is describe to plot, implement, and step-up study results. Type of this research is observational action braze, with use qualitative approaching and quantitatif one consisting of two cycles. Observational student of class four and observasional. Analisis’s result to learning planning on. Cycle is 73,21 %  experience step-ups on the second cycle, by derived 87,44 %. Result observinging to activity learns is learning on I, cycle is 70,39 % experiencestep-up on the second cycle  88,15 %. Result observinging to student activity in learning on I cycle is 66,22 % experience step-up on the second cycle, by derived  87,49 %. Studend learning outcomes first cycle was 69,86 in the second cycle to 84,57 The research action class uses Konstruktivisme could increase the student’s result for exact science ccourse.   Kata Kunci : hasil belajar, pembelajaran  IPA; pendekatan, konstruktivisme